The Reasons Why Accounting Student (Not) Pursuing Public Accounting Profession: A Systematic Literature Review - Diajeng Fitri Wulan; Reni Oktavia; Usep Syaipudin (Ilomata International Journal of Tax and Accounting, 2023)
The accounting industry is considered a good career choice and the ideal outcome for accounting graduates. However, the number of public accountants has decreased recently. The public accounting profession is declining due to several causes, including the need for more laws and legal protection for the industry, accounting reporting, and the small market share for audit services. The identification, screening, and selection phases of the systematic literature review process were used in this study to review previous research. The data analysis utilized in this study was predicated on the basis of the 21 papers that were found in the Google Scholar database and dated from 2006 to 2023. Students' decisions to pursue a career in public accounting are influenced by a number of different factors, according to the findings of a comprehensive evaluation of all of the research that was published between the years 2006 and 2023. Academics less frequently use regression to manage data than SEM analysis. Future research is expected to concentrate mainly on extending the use of variables as a factor influencing students' motivation to become public accountants and the approaches used